2013
DOI: 10.1111/ppl.12084
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of the ethylene biosynthesis in ‘Jonagold’ apple

Abstract: In this study, the short-term and dynamic changes of the ethylene biosynthesis of Jonagold apple during and after application of controlled atmosphere (CA) storage conditions were quantified using a systems biology approach. Rapid responses to imposed temperature and atmospheric conditions were captured by continuous online photoacoustic ethylene measurements. Discrete destructive sampling was done to understand observed changes of ethylene biosynthesis at the transcriptional, translational and metabolic level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
5
9
0
Order By: Relevance
“…Mango peel is considered a major location of polyphenols within the whole fruit . In agreement with the previous report by Kim et al ., the concentrations of total phenols in the peel were 36‐ and 8‐fold higher than pulp in ‘Kensington Pride’ and ‘R2E2’ mangoes, respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Mango peel is considered a major location of polyphenols within the whole fruit . In agreement with the previous report by Kim et al ., the concentrations of total phenols in the peel were 36‐ and 8‐fold higher than pulp in ‘Kensington Pride’ and ‘R2E2’ mangoes, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The production rate of ethylene was determined using a laser‐based photoacoustic ethylene detector (ETD‐300, Sensor Sense, Nijmegen, Netherlands) as explained earlier by Bulens et al . and expressed in pmol kg −1 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…There is extensive information regarding the ripening physiology (Bulens et al 2014) due to its biological, nutritional, and economical value. Except for a recent report on its predicted plastid proteome (Schaeffer et al 2014), not much is known about the novel proteomic or metabolomic constitution of apple plastids, which carry out important biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…CA reduces respiration and ethylene production, and preserves firmness and color of apples (Kader , Herregods ). Furthermore, previous studies conducted on specific segments of the metabolic pathway demonstrated the diverse and broad effect of O 2 and CO 2 in the electron transport chain (Nanos and Kader , Saquet et al ), glycolysis (Kerbel et al ), tricarboxylic acid (TCA) cycle (Shipway and Bramlage ), ethanolic fermentation (Ke et al ), Yang cycle (Bulens et al ) and amino acid metabolism (Hansen et al ). Low O 2 storage reduces cytosolic pH and energy charge of pears (Nanos and Kader ) and apples (Saquet et al ).…”
Section: Introductionmentioning
confidence: 99%
“…1‐MCP treatment combined with CA storage is more effective in maintaining the firmness of the fruit than 1‐MCP treatment with regular air (RA) storage (Watkins et al ). However, the efficacy of 1‐MCP depends on several factors such as cultivar, degree of maturity, treatment temperature and storage temperature and duration (DeEll et al , Blankenship and Dole , Bulens et al ). Also, 1‐MCP negatively influences aroma production (Ferenczi et al ), can have a positive, negative or negligible effect on soluble solid concentration (SSC) content (Watkins ), and increases the CO 2 injury (Fawbush et al ) and flesh browning of some apple cultivars such as ‘Empire’ apple (Jung and Watkins ).…”
Section: Introductionmentioning
confidence: 99%